ANALISIS PROFITABILITAS DENGAN RISIKO KREDIT SEBAGAI VARIABEL MODERASI PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Safitri, Ika Ayu; Nur, Dhani Ichsanuddin (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The banking sector in Indonesia plays a crucial role in the economy, where profitability is one of the main performance indicators. This study aims to analyze the influence of capital adequacy, liquidity, and Good Corporate Governance (GCG) on profitability, with credit risk as a moderating variable. The objects of this study are the banking sector listed on the Indonesia Stock Exchange (IDX). The population of the study includes all conventional banks listed on the IDX, with a sample selected using purposive sampling techniques, resulting in a total of 27 banking issuers during the observation period of 2019-2022. The research findings indicate that capital adequacy contributes to profitability, liquidity contributes to profitability, and GCG (Good Corporate Governance) contributes to profitability. Additionally, credit risk moderates liquidity towards profitability, and credit risk moderates GCG towards profitability, but it cannot moderate capital adequacy towards profitability. Keywords: Good Corporate Governance; Capital Adequacy; Liquidity; Profitability; Return on Assets; Credit Risk